Integrative and Complementary Practices in Health Promotion: A narrative review (Research, Society and Development, 2023)
Introduction: The Integrative and Complementary Health Practices (PICS) are presented as therapeutic methods seeking the prevention of diseases, improving the quality of life of individuals and collectivities. Objective: To analyze integrative and complementary practices in health promotion through a narrative review. Methodology: This is a narrative review on integrative and complementary practices in health promotion, carried out in June 2023. The search was carried out in the LILACS and BDENF databases, using the Health Sciences Descriptors (DeCS): "Integrative and Complementary Practices" AND "Health Promotion". A total of 120 articles were found, and 8 articles were selected to compose the study. Results and Discussion: Primary Health Care represents the gateway for users to health services, carrying the mission of articulating care practices and implementing PICS. It was observed that some nursing professionals in SUS health services perform practices such as auriculotherapy, acunputure and aromatherapy. The offer of these services triggers feelings of welcome, appreciation and recognition, providing a better quality of life. It was verified in the studies that the professionals emphasized that the academic formation is outdated of theoretical contribution about the PICS, demonstrating that it is necessary the initiative of the professional in training to meet the demands of these practices. Final Considerations: In view of the above, it was evident that the humanization of health care through PICS reinforces users' autonomy over their own health, promoting a better quality of life and ensuring individual and collective well-being.